Exploring the Correlation between Time Management, the Mediterranean Diet, and Physical Activity: A Comparative Study between Spanish and Romanian University Students. - Indreica Elena-Simona; Bădicu Georgian; Nobari Hady (My University, 2022)
Background: The investigation started from the premise that there are links between time management (TM), physical activity (PA), and the Mediterranean diet (MD). The aim of our study is to determine the correlation between the variables TM, the MD, and PA in Spanish and Romanian university students. Methods: The study was conducted on a group of 296 students (198 Romanian and 98 Spanish students between the ages of 23.44 ± 5.92 years, with 108 males and 188 females, where 171 were from the sports faculty and 125 were from the psychology faculty), using the Time Management Questionnaire (TMQ) to measure TM, the KIDMED test to measure MD, and the International Physical Activity Questionnaire-Short Form (IPAQ-SF) to measure PA. Results: The obtained results show that there are significant differences, regarding MD and PA, between the Romanian and Spanish respondents, between the respondents from the sports faculty and those from the psychology faculty, and between the female and male respondents. The TM variable did not show a significant difference depending on the country, faculty, or gender. There was only a significant relationship between the MD and the other two variables (TM and PA). Conclusions: Significant differences were observed between the variables the MD and PA, but not TM, depending on the country, gender, and faculty. There was only a significant correlation between the MD and the other two variables (TM and PA). The results provided us with relevant data for the need for a TM protocol to improve the MD adherence and PA in university students.
Keywords: nutrition; physical fitness; food habits; time management; quality of life